Culture Positivity and Antibiotic Resistance in Respiratory Intensive Care Patients: Evaluation of Readmission and Clinical Outcomes - Oral Menteş; Deniz Çelik; Murat Yildiz; Kerem Ensarioğlu; Maşide Ari; Mustafa Özgür Cırık; Abdullah Kahraman; Zehra Nur Şeşen; Savaş Gegin; Yusuf Taha Güllü (Diagnostics)
Background: Multidrug-resistant bacteria (MDRB) represent a significant challenge in intensive care units (ICUs), as they limit treatment options, prolong hospital stays, and escalate healthcare costs. Respiratory ICUs are particularly affected due to the high prevalence of chronically ill patients with recurrent infections. Understanding the impact of culture positivity and MDRB on clinical outcomes and readmission rates is essential for enhancing patient care and addressing the growing burden of antimicrobial resistance. Methods: This retrospective study was conducted in a specialized respiratory ICU at a tertiary care hospital between 1 January 2019, and 1 January 2020. A total of 695 ICU admissions were analyzed, with patients grouped based on readmission status and culture results. Demographic, clinical, and laboratory data were reviewed. Statistical analyses were performed using appropriate tests, with p-values ≤ 0.05 considered statistically significant. Results: Among the 519 unique patients, 65 experienced ICU readmissions. Male patients were significantly more likely to be readmitted (p = 0.008). Culture positivity was predominantly observed in respiratory samples, with Klebsiella spp. identified as the most common pathogen. MDRB prevalence exceeded 60% in both groups, significantly prolonging ICU stays (p = 0.013). However, no significant differences in survival rates were observed between MDRB-positive and MDRB-negative groups. Notably, patients with readmissions had lower C-reactive protein (CRP) levels both during admission and at discharge compared to non-readmitted patients (p = 0.004). This paradox may reflect a subclinical inflammatory response associated with bacterial colonization rather than active infection, particularly in patients with chronic respiratory diseases. Conclusions: MDRB infections and culture positivity are key contributors to prolonged ICU stays, resulting in increased healthcare costs. Implementing effective strategies to manage MDRB infections is critical for improving outcomes in respiratory ICUs and reducing associated risks. This study underscores the growing burden of MDRB and highlights the importance of enhanced antimicrobial stewardship in respiratory ICUs.